2012
DOI: 10.1038/npp.2012.193
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Behavioral and Pharmacological Treatment Strategies to Decrease Cocaine Choice in Rhesus Monkeys

Abstract: Behavioral and pharmacotherapeutic approaches constitute two prominent strategies for treating cocaine dependence. This study investigated interactions between behavioral and pharmacological strategies in a preclinical model of cocaine vs food choice. Six rhesus monkeys, implanted with a chronic indwelling double-lumen venous catheter, initially responded under a concurrent schedule of food delivery (1-g pellets, fixed-ratio (FR) 100 schedule) and cocaine injections (0-0.1 mg/kg/injection, FR 10 schedule) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…Moreover, the small, nonsignificant shifts in methamphetamine choice in the present study when the response requirement for both reinforcers was an FR100 are in contrast to previous results with cocaine. Under similar choice procedures, cocaine vs food choice was significantly attenuated with the FR response requirement matched at either FR100 or FR10 (Banks et al, 2013;Negus, 2003). Overall, the results of the present study are consistent with the results from a human laboratory methamphetamine choice study and suggest that methamphetamine choice may be less sensitive to response requirement 'cost' manipulations than cocaine choice.…”
Section: Baseline Methamphetamine Choice and Effects Of Environmentalmentioning
confidence: 99%
“…Moreover, the small, nonsignificant shifts in methamphetamine choice in the present study when the response requirement for both reinforcers was an FR100 are in contrast to previous results with cocaine. Under similar choice procedures, cocaine vs food choice was significantly attenuated with the FR response requirement matched at either FR100 or FR10 (Banks et al, 2013;Negus, 2003). Overall, the results of the present study are consistent with the results from a human laboratory methamphetamine choice study and suggest that methamphetamine choice may be less sensitive to response requirement 'cost' manipulations than cocaine choice.…”
Section: Baseline Methamphetamine Choice and Effects Of Environmentalmentioning
confidence: 99%
“…A 12-h light-dark cycle was in effect (lights on from 0600 to 1800 hours). All monkeys had prior cocaine selfadministration histories (Banks et al, 2013b;Banks et al, 2013c). Animal research and maintenance were conducted according to the 8th edition of the Guide for the Care and Use of Laboratory Animals as adopted and promulgated by the National Institutes of Health.…”
Section: Animalsmentioning
confidence: 99%
“…Choice behavior was considered stable when the lowest unit-cocaine dose maintaining at least 80% cocaine vs food choice varied by p0.5 log units for 3 consecutive days. Experimental parameters (unit-cocaine dose and dose order, alternative food reinforcer magnitude, and ratio requirement on food-and cocaine-associated keys) of the choice session used in this study were based on extensive parametric manipulations reported previously (Negus, 2003) and are identical to parameters used to assess other candidate medications effects on cocaine choice (Banks et al, 2011(Banks et al, , 2013bBanks et al, 2013c;Negus, 2004;Negus and Mello, 2004). Consequently, with the parameters used in this study, we could detect both leftward and rightward shifts in the cocaine vs food choice dose-effect function that might result from manipulation of experimental variables.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
See 2 more Smart Citations